2001
DOI: 10.1111/j.1574-6976.2001.tb00591.x
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study into the molecular methodology and molecular biology of methanogenic Archaea

Abstract: Methanogens belong to the kingdom of Euryarchaeota in the domain of Archaea. The Archaea differ from Bacteria in many aspects important to molecular work. Among these are cell wall composition, their sensitivity to antibiotics, their translation and transcription machinery, and their very strict demands to anaerobic culture conditions. These differences may, at least partly, be responsible for the delay in availability of genetic research tools for methanogens. At present, however, the research within genetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 146 publications
1
33
0
Order By: Relevance
“…Methanosarcina and Methanococcus species are facultative autotrophs that readily take up amino acids, and are therefore compatible with auxotrophic markers 74 . To enable full exploitation of auxotrophic markers, it is best if the organism can be grown on chemically defined (minimal) medium, as is the case for P. abyssi 75 ,…”
Section: Transformationmentioning
confidence: 99%
“…Methanosarcina and Methanococcus species are facultative autotrophs that readily take up amino acids, and are therefore compatible with auxotrophic markers 74 . To enable full exploitation of auxotrophic markers, it is best if the organism can be grown on chemically defined (minimal) medium, as is the case for P. abyssi 75 ,…”
Section: Transformationmentioning
confidence: 99%
“…While genetic methodology has been developed for methanogenic archaea (19,34) and extremely halophilic archaea (24,34), comparable to those of their bacterial counterparts, manipulative strategies for the hyperthermophilic archaea are still at an early stage. With respect to the genus Sulfolobus in the kingdom Crenarchaeota, various genetic elements have been identified (44), and natural gene transfer via conjugation (26,31) or virus infection (32) has been observed.…”
mentioning
confidence: 99%
“…have been isolated from cold habitats (Franzmann et al 1992(Franzmann et al , 1997Simankova et al 2003). Although the metabolism of methanogenic archaea has been studied in different environments (Ni and Boone 1998;Garcia et al 2000;Eicher 2001;Lange and Ahring 2001), only a few studies have focussed on the ecology of the methanogenic archaea in permafrost ecosystems (Vishnivetskaya et al 2000;Høj et al 2005). Studies have shown that methanogenic archaea from Siberian permafrost are well adapted to osmotic stress and are also highly resistant to inactivation by desiccation, radiation, extremely low temperatures (Morozova and Wagner, data under processing) and high oxygen partial pressure (Wagner et al 1999).…”
Section: Introductionmentioning
confidence: 99%